Analysis of Various Marketing Strategies for Wedding Organizer PT. Pratoza Kreasi Nusantara To Increase Consumer Purchase Interest - Wardi Saputra , Wardi Saputra; Tri Suratmi, Tri Suratmi; Maryati Tamba, Maryati Tamba (Journal of Entrepreneur and Business, 2023)
Pratoza Kreasi Nusantara is engaged in services, one of which is the Wedding Organizer "Promise Marriage", which serves every consumer who wants to hold a traditional or non-traditional wedding ceremony. This study aims to analyze various strategies in increasing consumer buying interest. Data were collected through filling out questionnaires using a purposive sampling technique with a population of 222 people as respondents. Analysis of the data used in this study is SEM-PLS (Partial Least Square). The results of this study indicate that several of the hypotheses tested gave positive and negative results, positive hypotheses were found in the Word of Mouth, Facilities and Services variables. While the results of the negative hypothesis are found in the price variable, partially there are hypotheses that have an effect and some have no effect on Buying Interest The conclusion of this study is that the various strategies carried out have a positive effect and some have a negative effect on buying interest. Suggestions from this research that Wedding Organizer PT. Pratoza Kreasi Nusantara " Janji Nikah" pays more attention to the price of the wedding package so that it can be more balanced. So that customers get a price that suits their budget. This can be done by stabilizing the quality of wedding packages, such as making packages ranging from middle to high and middle to lower packages. Key Word : Word of Mouth, Facility, price, service, buying interest.